Respuesta :

First of all, this is a probability question,so you must memorize the rules.

P(B)=P(AUB)+P(A int. B)-P(A)

=0.8+0.4-0.5

P(B)=0.7

Therefore, P(B).P(B)=0.7*0.7=0.49

Answer:

P(B) = 0.7

Step-by-step explanation:

for events that are NOT mutually exclusive,  the following applies:

P(A∪B) = P(A) + P(B) - P(A∩B)

in our case we can see that P(A∩B) is given as non-zero, hence the events are not mutually exclusive and the above formula can be used.

Given:

P(A) = 0.5

P(A∪B) = 0.8

P(A∩B) = 0.4

Substituting these into the above equation

P(A∪B) = P(A) + P(B) - P(A∩B)

0.8 = 0.5 + P(B) - 0.4

0.8 = 0.1 + P(B)   (subtract 0.1 from both sides)

P(B) = 0.8 - 0.1 = 0.7